Kartagener Syndrome Associated with a Family History of Dextrocardia – First Patient to be reported in Romania - Catana, Andreea; Kutasi, Eniko; Chis, Florica Ana; Popita, Cristian; Militaru, Sanda Mariela (Archives of Clinical and Biomedical Research, 2022)
Kartagener syndrome is a monogenic inherited disorder in the heterogenous group of primary diseases of the cilia, with pulmonary and ENT (ear/nose/throat) involvement, situs inversus, and infertility. The condition is characterized by the clinical triad consisting of bronchiectasis, situs inversus, and chronic sinusitis. Most cases result from biallelic mutations in DNAH5 and DNAI1 genes, which encode the outer dynein arm, responsible for microtubule movement in cells. We are reporting a 14-yearold male patient who underwent genetic testing at 14, despite recurring sinus and ear infections from a very young age. A recently performed CT scan revealed dextrocardia, and further imagistic investigations showing situs inversus and genetic testing defined a compound heterozygous genotype for the DNA11 gene as Kartagener syndrome was confirmed. Heterozygous pathogenic variants were identified in both parents and the patient’s brother. The case report provides details regarding the patient's diagnosis, the medical particularities of the case due to genotype-phenotype associations, and the psycho-emotional impact related to the diagnosis of a rare genetic disease. Potentially relevant family history is also discussed. This is the first patient with Kartagener syndrome to be reported and published in Romania.